Analisis Total Productive Maintenance pada Mesin Laminating I dengan Metode Overall Equipment Effectiveness - Zulkani Sinaga; Tri Maryanto (Universitas Bunda Mulia, 2019)
This research was conducted on one of the giant manufacturers of musical instrument equipment that is inseparable from problems related to the effectiveness of the machine/equipment caused by the six big losses. The improper handling and maintenance of the machine can result in losses called the six big losses. The first stage in the effort to increase production efficiency in this company is to measure the effectiveness of laminating machine I using the overall equipment effectiveness (OEE) method which is then followed by measuring the OEE six big losses to find out the amount of efficiency lost in the six big losses. From these six factors, then what factors are found to give the greatest contribution that result in the large amount of efficiency lost in laminating machines I. The causal diagram can be analyzed the real problem which is the main cause of high losses resulting in low efficiency on laminating-machine I. Conclusions that can be taken on laminating machine I that the OEE value for the period April 2016 to March 2017 ranged from 61.08% to 83.91%. This condition indicates that the ability of laminating-machine I to achieve targets and achieve effectiveness has not reached the ideal condition (≥86%). As for those that affect the OEE value and become the top priority, the reduced speed factor is 78.79%.